ANALISA TINGKAT PELAYANAN JALAN SUNAN KALIJAGA KELURAHAN DINOYO KECAMATAN LOWOKWARU KOTA MALANG - Suhudi Suhudi; Alfian Tenabolo (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2017)
Malang city is the second big city after Surabaya City in East Java with tourist potential and its economy is growing. The activities such as malls, markets, parks, campuses, tourist areas, office activities and other activities are factors that make this street has a solid activity resulting transportation problems one bottleneck that resulted in road capacity has declined, Survey or research used method of retrieval Data with Manual Method Counter at Sunan Kalijaga Street, Dinoyo Village, Lowokwaru District, Malang City for the purpose of calculating the value of the traffic volume, speed, capacity and level of service is to conduct a survey for 6 days (starting at 06.00 am – 21.00 pm) and the data obtained from the survey of traffic volume, vehicle speed and road geometric data were then analyzed using the Indonesian Highway Capacity Manual (IHCM) 1997. Based on the analysis, peak hour volume on Sunan Kalijaga Street was 1887 pcu / h, the average speed (V) is 75.784 m / sec, a capacity of 1262, 77 and the level of service (LOS) is F.